INFORMATION TOOLS FOR INTEGRATED PUBLIC PASSENGER TRANSPORT (Perner's Contacts, 2011)
The paper deals with an issue of information for passenger and applied information tools in integrated public passenger transport systems. Attention is focused on general issues, on the groups of information needs, on the information tools for common passengers and special groups of passengers and at last on requirements for the website of integrated public passenger transport.